Niewidomy student anglistyki i jego wykładowca: potrzeby, wyzwania, techniki - Buczek-Zawiła, Anita (Neofilolog, 2011)
It is generally postulated that visually-impaired students should be in-volved in mainstream study programs, along their sighted co-students. In the context of English Philology, this means that lecturers need to adapt their tutorials, their teaching aids, their techniques and general attitude. It is advocated here that it can be done even when lecturers are not trained in the field of SEN. The success of their students depends largely on the lecturers resourcefulness and creativity, as well as on their willingness to devote extra time to meeting the needs of such students.